PENGARUH FIRM SIZE, SALES GROWTH, STRUKTUR ASET, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2012 – 2017) - Suci Atiningsih; Asri Nur Wahyuni (Sekolah Tinggi Ilmu Ekonomi Semarang, 2020)
The purpose of this study is to examine the effect of firm size, sales growth, asset structure, and profitability on firm value with capital structure as an intervening variable. The population are all companies listed on the Indonesia Stock Exchange. While the sample in this study were all manufacturing companies listed on the Indonesia Stock Exchange Period 2012 - 2017. Sampling using purposive sampling and data analysis methods using multiple linear regression and path analysis. The results of this study are firm size and asset structure have a positive effect on capital structure. Sales growth and profitability have a negative effect on capital structure. Capital structure, sales growth, and asset structure have a negative effect on firm value. Firm size has a positive effect on company value. Capital structure cannot mediate the influence of firm size and profitability on firm value. Capital structure can mediate the effect of sales growth and asset structure on firm value.